The vital role of covS in the establishment of Streptococcus equi subsp. zooepidemicus virulence - Bin XU; Zhe MA; Hong ZHOU; Hui-xing LIN; Hong-jie FAN (Journal of Integrative Agriculture, 2023)
Streptococcus equi subsp. zooepidemicus (SEZ) is an important zoonotic agent. Here, a virulence-attenuated strain M35246 derived from natural variation of wild-type SEZ ATCC35246 was found. M35246 showed a deletion of 25 contiguous genes as well as a loss-of-function mutation in covS. Subsequently, a 25-gene-deleted strain (ΔPI), a covS-mutant strain (McovS), and relevant complementary strains were constructed and investigated. M35246 and McovS were significantly less encapsulated and exhibited poorer anti-phagocytic capacity compared to wild-type SEZ. McovS was significantly more sensitive to β-lactams, aminoglycosides, macrolides, and lincosamides than wild-type SEZ. M35246, McovS, and ΔPI exhibited an increase in median lethal dose (LD50) in mice by 105, 105, and 5 times when compared to wild-type SEZ, respectively. Neither M35246 nor McovS were isolated from mice 48 h after being challenged with approximately 2 000 times the LD50 of wild-type SEZ. Transcriptome analysis showed that 668 significantly differentially expressed genes existed between McovS and wild-type SEZ. Numerous virulence factor-encoding genes and anabolic-related genes in McovS that were involved in anti-phagocytosis, capsule formation, pathogenicity, and antibiotic resistance were downregulated significantly relative to the wild-type strain. This study revealed that the CovS plays a vital role in the establishment of SEZ virulence.